Reconstructing the Intangible Cultural Heritage of the Moravian Missions - Eyerly, Sarah (Journal of Moravian history, 2022)
This article discusses the application of digital sound technologies within the field of Moravian studies through the case study of Moravian Soundscapes, a digital companion project to the book Moravian Soundscapes: A Sonic History of the Moravian Missions in Early Pennsylvania (Bloomington: Indiana University Press, 2020). Through sound recordings, digital and historic maps, and archival materials from the Moravian Archives in Bethlehem, Pennsylvania, and Herrnhut, Germany, as well as place-based photography, the project documents and reconstructs the soundscapes of eighteenth-century Moravian mission communities in eastern Pennsylvania. The article advocates for the use of sound mapping and sound reconstructions as important methods for understanding the intangible cultural heritage of early Moravian communities.